2021
DOI: 10.2147/jpr.s315360
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes After Breast Cancer Surgery Between Inhalational and Propofol-Based Intravenous Anaesthesia: A Systematic Review and Meta-Analysis

Abstract: Background: General anaesthesia is the commonly provided for breast cancer surgery, but the effects of inhalational anaesthesia and propofol-based intravenous anaesthesia on shortand long-term outcomes after breast cancer surgery are not clear. In this study, we conduct a meta-analysis of randomized controlled trials (RCTs) to explore the superior anaesthetic for breast cancer surgery patients. Methods: We searched the Embase, Medline, Cochrane Library, Web of Science, CNKI, and Wanfang databases (up to Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Levobupivacaine and ropivacaine reduced tumor cell invasion and migration by reducing RhoA protein levels (Castelli et al, 2020). Some studies showed that sodium channel blockade contributed to the anticancer activity of LAs (Fraser et al, 2014), but these studies also demonstrated that bupivacaine inhibited the migration of gastric cancer cells via the sodiumindependent channel blocker RhoA and NET1 inhibition (Dan et al, 2018;Zheng et al, 2020;Pang et al, 2021). These results suggest that LAs are associated with the RhoA and NET1 pathways in addition to sodium channel blockade.…”
Section: Inhibition Of Ras Homolog Gene Family Member a Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Levobupivacaine and ropivacaine reduced tumor cell invasion and migration by reducing RhoA protein levels (Castelli et al, 2020). Some studies showed that sodium channel blockade contributed to the anticancer activity of LAs (Fraser et al, 2014), but these studies also demonstrated that bupivacaine inhibited the migration of gastric cancer cells via the sodiumindependent channel blocker RhoA and NET1 inhibition (Dan et al, 2018;Zheng et al, 2020;Pang et al, 2021). These results suggest that LAs are associated with the RhoA and NET1 pathways in addition to sodium channel blockade.…”
Section: Inhibition Of Ras Homolog Gene Family Member a Migrationmentioning
confidence: 99%
“…Rho and RAC GTP enzymes regulate all types of cell migration ( Zheng et al, 2020 ), and one of the activators of the Ras homolog gene family member A (RhoA) pathway is neuroepithelial cell gene 1 (NET1) ( Pang et al, 2021 ). Rho-associated protein kinase (Rock) is a downstream effector of the RhoA pathway.…”
Section: Effects Of Local Anesthetics On Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2 ) The mechanisms through which anesthetic-analgesic techniques influence breast cancer outcomes have increasingly garnered attention although the results of research have been inconsistent. ( 3 11 )…”
Section: Introductionmentioning
confidence: 99%
“…(2) The mechanisms through which anesthetic-analgesic techniques influence breast cancer outcomes have increasingly garnered attention although the results of research have been inconsistent. (3)(4)(5)(6)(7)(8)(9)(10)(11) Tramadol is a centrally acting analgesic that is widely accepted in the treatment of moderate postoperative pain. ( 12) Piñero and colleagues (13) reported that b-adrenoceptor agonists and a 2adrenoceptor antagonists can effectively suppress breast cancer cell proliferation and tumor growth via the inhibition of extracellular signal-regulated kinase 1/2 (ERK 1/2) phosphorylation in an animal model.…”
Section: Introductionmentioning
confidence: 99%